2014
DOI: 10.1016/j.radonc.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric predictors of esophageal toxicity after stereotactic body radiotherapy for central lung tumors

Abstract: Background and Purpose Stereotactic body radiotherapy (SBRT) to central lung tumors can cause esophageal toxicity, but little is known about the incidence or risk factors. We reviewed central lung SBRT patients to identify dosimetric factors predictive of esophageal toxicity. Material and Methods We assessed esophageal toxicity in 125 SBRT patients. Using biological equivalent doses with α/β=10 Gy (BED10), dose-volume histogram variables for the esophagus (Dv and Vd) were assessed for correlation with grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…This is in line with an earlier report where the diverse DVH parameters were replaced by the esophageal D mean resulting in a validated AET predictive model [11]. Thus, D mean seems an adequate surrogate DVH parameter for nonstereotactic techniques, however, for modeling of AET after stereotactic radiotherapy for central lung tumors the maximum dose to the esophagus and doses to small volumes correlate best with AET [35].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with an earlier report where the diverse DVH parameters were replaced by the esophageal D mean resulting in a validated AET predictive model [11]. Thus, D mean seems an adequate surrogate DVH parameter for nonstereotactic techniques, however, for modeling of AET after stereotactic radiotherapy for central lung tumors the maximum dose to the esophagus and doses to small volumes correlate best with AET [35].…”
Section: Discussionsupporting
confidence: 88%
“…Modh et al 36 reported that 12.8% patients with central lung tumour experienced $ grade 2 oesophageal toxicity after SBRT treatment. Wu et al 37 found that the incidence of grade $2 acute toxicity was 12%. In these cases, the use of 6XFFF beam will lower the incidence rate of oesophageal toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the use of 6XFFF beam will lower the incidence rate of oesophageal toxicities. The newly introduced SBRT was reported with higher incidence of complications than conventional techniques, 4 such as pulmonary toxicity, 24,[38][39][40][41] CW pain 24,25,31,42 and oesophageal toxicity, 37 especially when the target was adjacent to the OARs. Previous studies found that V 5 , V 10 , V 20 and mean lung dose (MLD) were predictive of radiation pneumonitis (RP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, clinical studies have demonstrated that RT dose, fractionation, dosevolume histogram constraints, as well as administration of systemic therapy are related to toxicity [47][48][49]. We caution clinicians to consider lymph node station (particularly zone 7) and use of previous RT before administration of SRT for R/SP-MLNMs.…”
Section: Discussionmentioning
confidence: 99%